Using a Modified Parent-Child Interaction Therapy to Increase Vocalizations in Children With Autism. Issue 4 (1st October 2016) - Hansen, Bethany; Shillingsburg, M. Alice
ABSTRACT: Parent-Child Interaction Therapy (PCIT) is a manualized behavioral intervention originally developed by Eyberg (1988 ) to address disruptive behaviors in young children. Although previous research findings support the contention that components of PCIT would positively impact communication, behavior, and adaptive skills (Howard, Sparkman, Cohen, Green, & Stanislaw, 2005; Lovaas, 1987 ; Remington et al., 2007 ) in children with developmental disabilities, few studies are shown in the literature. In a modified version of PCIT, caregivers completed two phases of intervention with their child diagnosed with Autism Spectrum Disorder (ASD). During the Child-Directed Interaction (CDI) phase, caregivers were taught to conduct mand training, follow-their child's lead, provide attention for their child's positive behaviors, and ignore their child's negative behaviors. During the Parent-Directed Interaction (PDI) phase, caregivers were taught to give effective commands and follow through with demands. The goal of the current study was to determine whether children's production of vocalizations increased after participation in a modified PCIT program. Data from two participants diagnosed with autism were included in the study. Outcomes of these two case studies show that both children displayed an increase in the total number of vocalizations emitted in the posttreatment observation relative to baseline. Additionally, caregivers of both participants displayed an increased number of positive behaviors in the posttreatment observation relative to baseline.